Two graves with cremation burials from Ptuj - Dular, Janez; Lubšina Tušek, Marija (Arheološki vestnik, 2014)
Two interesting graves with cremation burials from Ptuj are presented in the article, which differ from the usual grave of the Ruše Urnfield group in terms of the grave goods. The gradual stratification of society is reflected in them, which acquired a new form with the onset of the Early Iron Age.